Volume 2: 28th Design Automation Conference 2002
DOI: 10.1115/detc2002/dac-34119
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Optimisation Using Real Options Theory and Dependency Structure Matrices

Abstract: This paper outlines a methodology for optimising the multi-domain architecture of a relatively integrated system through an appropriate level of modularisation to maximise societal value created. This method is developed through the application of real options theory and the dependency structure matrix (DSM), and illustrated using a reference example of an industrial gas turbine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This is because it is easiest to inspect, and because the physical domain often maps closely to the task domain so arranging it in this way eases the process of comparison. This point is expanded upon by Sharman, Yassine, and Carlile [2002], regarding interdomain mapping. Third, many runs of the Thebeau clustering algorithms failed to reveal this clustering solution.…”
Section: Applying Dimensionality To the Gas Turbinementioning
confidence: 98%
“…This is because it is easiest to inspect, and because the physical domain often maps closely to the task domain so arranging it in this way eases the process of comparison. This point is expanded upon by Sharman, Yassine, and Carlile [2002], regarding interdomain mapping. Third, many runs of the Thebeau clustering algorithms failed to reveal this clustering solution.…”
Section: Applying Dimensionality To the Gas Turbinementioning
confidence: 98%
“…The objective function is therefore a trade-off between the cost of being inside a module and the overall system benefit. Sharman et al (2002) attempted using Fernandez's algorithm on an industrial gas turbine. However, they showed that this algorithm is incapable of predicting the formation of good clustering arrangements for complex product architectures due to the oversimplification of the objective function.…”
Section: Dependency Structure Matrix (Dsm) Methodsmentioning
confidence: 99%
“…Eppinger and Salminen [8] discuss the possible relationship between the product, tasks, and organizational domains in product development. Sharman et al [22] suggest that elements in one domain need to map to the same element in another domain in a one-to-one manner. They propose a hypothetical optimization of a multiple-domain PD project resulting in an optimal design structure matrix (DSM) showing the relational arrangement of elements within the domains.…”
Section: Literature Reviewmentioning
confidence: 99%